Health care professionals' perspectives of living and dying with primary malignant glioma: Implications for a unique cancer trajectory. Issue 6 (21st October 2013) - Philip, Jennifer; Collins, Anna; Brand, Caroline A.; Gold, Michelle; Moore, Gaye; Sundararajan, Vijaya; Murphy, Michael A.; Lethborg, Carrie
Abstract: Objectives: Health care professionals (HCPs) caring for people with primary malignant glioma (PMG) and their carers see many of the profound challenges facing this group, yet their perspectives are not documented. This study aimed to understand and document the unique perspective of HCPs in relation to the supportive and palliative care needs of patients with PMG and their carers, with a view to developing a model of care. Methods: Qualitative study involving semi-structured focus groups and interviews with 35 medical, nursing and allied health staff actively engaged in providing care for this patient group. Purposive and theoretical sampling from two major metropolitan hospitals and one community palliative care service in Australia was utilised to seek perspectives from a variety of disciplines and health care settings. Thematic analysis was conducted by three independent researchers, using a constant comparative method influenced by grounded theory. Results: Key themes relating to the needs of people with PMG which were apparent from the HCPs included: The difference in the illness course of glioma compared to other cancers; Limitations of current medical care; Challenges in balancing hope with reality of the illness; and Recommendations to improve care, including recognising the role of family and moving from a model where services are offered in response to demonstrated needs. Significance of the results: Current models of care based upon the classic cancer trajectory are unresponsive to the needs of people with PMG. Care may be enhanced by moving towards a proactive approach, extending the goals of care beyond medical needs and broadening the focus of care to include family needs.